Evaluasi Tingkat Kematangan Tata Kelola Ti Di Pos Kediri Menggunakan Cobit 5 - Ahmad Muharram Alfarisi; Rini Indriati; Dwi Harini (LPPJPHKI Universitas Dehasen Bengkulu, 2026)
Kediri Post Office, as a public organization that provides vital communication and financial services to the community, requires well-developed and effective information technology (IT) infrastructure and management. However, no comprehensive evaluation of the maturity level of IT governance has previously been conducted to identify the current condition and potential areas for improvement. This study aims to evaluate the maturity level of IT governance at Kediri Post Office using the COBIT 5 framework across three main domains (APO, DSS, and MEA), with a focus on identifying gaps and providing recommendations for process improvement. The research employed a qualitative approach, with data collected through in-depth interviews, field observations, and document analysis to validate the implementation of IT processes within the organization. The evaluation results indicate that the overall IT governance maturity level at Kediri Post Office is at Level 2 (Repeatable Process), with an average score of 2.33 on a scale of 0–5. Two processes have achieved Level 3 (Established Process), namely APO03 (Manage Enterprise Architecture) and DSS02 (Manage Service Requests and Incidents), while the remaining seven processes are still at Level 2. Gap analysis revealed an average gap of 0.89 levels compared to the target maturity level of 3.33. The primary issues identified include incomplete formal documentation, inconsistent process formalization across organizational units, and monitoring and evaluation mechanisms that are not yet systematic, particularly within the MEA (Monitor, Evaluate, and Assess) domain.